Volatility Transmissions between Oil Prices and Emerging Market Sectors: Implications for Portfolio Management and Hedging Strategies - Demiralay, Sercan; Gencer, Hatice Gaye (International Journal of Energy Economics and Policy, 2014)
This paper investigates the mechanisms of return and volatility transmissions between oil prices and five emerging market sector returns. For the empirical method, we utilize a recent and novel technique: Vector Autoregressive-Asymmetric GARCH (VAR-AGARCH) model. We find some significant cross shock and volatility linkages between oil prices and the sectors. However, our results manifest that the sector indices are not affected equally or simultaneously by movements in oil prices. Additionally, we compute the optimal holding weights and hedge ratios for the two-asset portfolio consisting of oil and each sector index. Our empirical findings have potential implications for investors and portfolio managers. Keywords: Emerging sector indices; oil prices; volatility transmission; optimal weights; hedge ratios JEL Classifications: C32; G11